2020
DOI: 10.3390/ijms21197025
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Stromal Periostin Expression in Non-Small Cell Lung Cancer

Abstract: Background: The microenvironment of solid tumours is significant in cancer development and progression. The aim of this study was to determine periostin (POSTN) expression by cancer-associated fibroblasts (CAFs) in non-small-cell lung cancer (NSCLC), as well as to assess associations with clinicopathological factors and prognosis. Materials and Methods: Immunohistochemical analysis of POSTN expression was performed on NSCLC (N = 700) and non-malignant lung tissue (NMLT) (N = 110) using tissue microarrays. Lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…Our results confirmed the increased expression of POSTN in cancer cells of NSCLC compared to NMLT, suggesting that POSTN could be related to the process of carcinogenesis in NSCLC. The results of the present study are in line with our previous observations regarding POSTN expression in cancers cells of invasive ductal carcinoma (IDC) [35] as well as in the stromal compartment (CAFs) of NSCLC [24]. Moreover, LCM, which was used to determine the POSTN mRNA expression levels in NSCLC cancer cells, confirmed the TMA IHC observations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results confirmed the increased expression of POSTN in cancer cells of NSCLC compared to NMLT, suggesting that POSTN could be related to the process of carcinogenesis in NSCLC. The results of the present study are in line with our previous observations regarding POSTN expression in cancers cells of invasive ductal carcinoma (IDC) [35] as well as in the stromal compartment (CAFs) of NSCLC [24]. Moreover, LCM, which was used to determine the POSTN mRNA expression levels in NSCLC cancer cells, confirmed the TMA IHC observations.…”
Section: Discussionsupporting
confidence: 92%
“…The correlation analysis showed a strong positive significant (r = 0.7085, **** p < 0.0001) correlation of POSTN expression in the cytoplasm of cancer cells with POSTN expression in tumor stromal cells (CAFs) in the whole cohort (Figure 5A). The results of POSTN expression in the stromal cells (CAFs) were used from previously conducted and published studies [24]. Furthermore, we also noticed a strong positive significant correlation between epithelial POSTN expression and the level of POSTN expression in stromal cells in AC and SCC subtypes (r = 0.7897, r = 0.6607, **** p < 0.0001, respectively) (Figure 5B,C).…”
Section: Associations Between Cytoplasmic and Stromal Expression Of P...supporting
confidence: 61%
See 1 more Smart Citation
“…A recent study reported that TIMP1 knockdown using short hairpin RNA in gemcitabine (GEM)-resistant pancreatic ductal adenocarcinoma cells enhanced GEM sensitivity and reversed chemoresistance by inducing cell apoptosis ( 39 ). POSTN expresses extracellular matrix periostin, which is involved in the activation of the PI3K/Akt signaling pathway ( 40 , 41 ) and was found to be an independent negative prognostic factor in non-small cell lung carcinoma ( 42 ). In addition, POSTN protein expression has been confirmed to be positively associated with cancer drug resistance ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment (TME) is a special environment for tumor proliferation that is composed of tumor cells, endothelial cells, tumor stromal cells, ECM, and various factors 28 . POSTN, as an ECM protein, is highly expressed in the stromal cells around the cancer epithelium, 29 promoting the occurrence, metastasis, and progression of tumors by establishing and remodeling the TME 30 . POSTN can induce epithelial–mesenchymal transition in lung cancer by activating the p38/ERK pathway and inhibiting the expression of microRNA‐381 that targets both Snail and Twist 31 .…”
Section: Discussionmentioning
confidence: 99%